The congrid eel genus Bathycongrus of Taiwan, with descriptions of three new species (Anguilliformes: Congridae) - Smith, David G.; Ho, Hsuan-Ching (Zootaxa, 2018)
Ten species of the congrid eel genus Bathycongrus are recognized from Taiwanese waters. Diagnoses and full descriptions of eight species are provided in present work. Three species are described as new. Bathycongrus bimaculatus sp. nov. is a small species with a pale body color, two black patches on dorsal fin, and 109–111 total vertebrae. Bathycongrus graciliceps sp. nov. is a moderately elongate species with a small, slender head and long trunk, and 163 total vertebrae. Bathycongrus castlei sp. nov. is a slender species with a relatively short trunk, dorsal half of body deep brownish, and 160–162 total vertebrae. Two rare species, B. bleekeri Fowler, 1934 and B. macroporis (Kotthaus, 1968), are newly reported from Taiwan. A key to all species in Taiwan is provided.